A Novel Trafficking Signal within the HLA-C Cytoplasmic Tail Allows Regulated Expression Upon Differentiation of Macrophages - Schaefer, Malinda R. (2008)
Major histocompatibility complex class I molecules (MHC-I) present peptides to cytotoxic T lymphocytes (CTLs). In addition, HLA-C allotypes are recognized by killer cell Ig-like receptors (KIR) found on natural killer (NK) cells and effector CTLs. Compared to other classical MHC-I allotypes, HLA-C has low cell surface expression and an altered intracellular trafficking pattern. We present evidence that this results from effects of both the extracellular domain and the cytoplasmic tail. Notably, we demonstrate that the cytoplasmic tail contains a dihydrophobic (LI) internalization and lysosomal targeting signal that is partially attenuated by an aspartic acid residue (DXSLI). In addition, we provide evidence that this signal is specifically inhibited by hypophosphorylation of the adjacent serine residue upon macrophage differentiation and that this allows high HLA-C expression in this cell type. We propose that tightly regulated HLA-C surface expression facilitates immune surveillance and allows HLA-C to serve a specialized role in macrophages.